Brachiopods from off the San Bernardo Archipelago (Colombian Caribbean), with comments on specific synonymies in Tichosina Cooper, 1977 - Rojas, Alexis; Gracia, Adriana; Patarroyo, Pedro (Zootaxa, 2015)
Colombian brachiopod faunas have not been studied extensively. Only three brachiopod species have been reported from the Colombian Caribbean Sea so far, namely Argyrotheca barrettiana (Davidson, 1866), Terebratulina latifrons Dall, 1920, and the cosmopolitan Platidia anomioides (Scacchi & Philippi, 1844). In this work, brachiopods collected from deep-water environments (90–250 m) off the San Bernardo Archipelago, collected during the MARCORAL cruise, are examined. The studied material consists of four species, two of which are new records for Colombia: Terebratulina cailleti Crosse, 1865 and Tichosina plicata Cooper, 1977. The genus Tichosina belongs to the family Terebratulidae and comprises twenty extant species occurring across the Caribbean. Based on a revision of published descriptions and illustrations, we synonymize Tichosina bullisi Cooper, 1977 and Tichosina dubia Cooper, 1977 with Tichosina plicata Cooper, 1977. Remarkably, apart from reports from southern Guiana, T. plicata is restricted to the margins of the Caribbean plate.